Foresight methodologies: application to the housing market - Eduardo Castro; Joao Lourenço Marques; Monique Borges (European Regional Science Association (ERSA), 2012)
The housing market is complex, multidimensional and depends on the variability of external factors and the amount of information available to the agents involved in the process. Despite the challenges associated to this theme, its relevance in the socioeconomic and territorial context, sustains a greater effort to develop and apply knowledge for decision making; process that depends on the evolution of the factors influencing the housing market. The formal analytical models that have been applied limit the ability to introduce the uncertainty of the future, which enhances the contribution of foresight analysis, as a strategic tool that supports the construction of future visions in order to inform decision making. The project "Drivers of Housing Demand in Portuguese Urban System" (DONUT) studies the housing market dynamic and analyses the housing price explanatory factors, combining econometric models with foresight analysis (future scenarios and Delphi techniques). This paper discusses the importance of using foresight techniques as a decision support tool, being presented an exploratory exercise of future scenario analysis. For this purpose, the paper is structured in three parts: i) brief description of the predicting models, ii) summarized approach to the housing market in the context of future scenarios and introduction of the dimensions chosen for the exercise, iii) short description of the scenarios.
Keywords: 330